Enabling n-type polycrystalline Ge junctionless FinFET of low thermal budget by in situ doping of channel and visible pulsed laser annealing. (30th January 2017) - Huang, Wen-Hsien; Shieh, Jia-Min; Kao, Ming-Hsuan; Shen, Chang-Hong; Huang, Tzu-En; Wang, Hsing-Hsiang; Yang, Chih-Chao; Hsieh, Tung-Ying; Hsieh, Jin-Long; Yu, Peichen; Yeh, Wen-Kuan
Abstract: A low-thermal-budget n-type polycrystalline Ge (poly-Ge) channel that was prepared by plasma in-situ-doped nanocrystalline Ge (nc-Ge) and visible pulsed laser annealing exhibits a high electrically active concentration of 2 × 10 19 cm −3 and a narrow Raman FWHM of 3.9 cm −1 . Furthermore, the fabricated n-type poly-Ge junctionless FinFET (JL-FinFET) shows an I on / I off ratio of 6 × 10 4, V th of −0.3 V, and a subthreshold swing of 237 mV/dec at V d of 1 V and DIBL of 101 mV/V. The poly-Ge JL-FinFET with a high-aspect-ratio fin channel is less sensitive to V th roll-off and subthreshold-swing degradation as the gate length is scaled down to 50 nm. This low-thermal-budget JL-FinFET can be integrated into three-dimensional sequential-layer integration and flexible electronics.